Keberlangsungan UMKM Saat Ada dan Tidaknya Tiktok Shop Prespektif Persaingan Pasar Syariah (Studi Di Pasar Panorama Kota Bengkulu) - Aldo Aldo; Desi Isnaini; Nurrahmah Putry (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Based on the perspective of sharia market competition, the aim of the research is to find out the sustainability of MSMEs in the Panorama market of Bengkulu city when there are and are not TikTok shops based on the perspective of sharia market competition. To find out how efforts are made by MSME players in the Panorama market of Bengkulu city. in facing market competition when there is or is not a TikTok shop based on the perspective of sharia market competition. The type of research used is field research with data collection methods, namely observation, interviews and documentation with a descriptive qualitative approach in analyzing the data. The subjects in this research are MSME traders in the Bengkulu City Panorama Market. The results that emerge from this research are the sustainability of MSMEs in the Bengkulu City Panorama Market when there are no TikTok shops. The Bengkulu City Panorama Market MSMEs do not manage employees and customers, lack of product innovation and sales, some even don't do it at all, lack of creativity and innovation among MSME players, dishonesty and openness regarding purchasing capital and profits taken, related to the efforts made by MSME players, including continuing to sell at the stalls they own. do not try to compete by selling on TikTok shops or other e-commerce, while a small part of the traders only post normally on Whatsapp, Facebook and Instagram. Therefore, if viewed from the perspective of sharia market competition, the things mentioned above are not in accordance with Fatahana's nature, namely professionalism. and tabigh, namely conveying things about the product truthfully.